Over a million students use our free study notes to help them with their homework
To rationalise a fraction we have to eliminate the surds in the denominator. We know we can multiply the top and the bottom of a fraction by the same thing, as this is equivalent to multiplying by 1. Noti...
First of all you calculate dy/dx. To do this you look at each x individually. For the first x you multiply it by it's power and then minus 1 from the power to get 3x^2. Then multiply the next x by the pow...
because the equation is made up of two functions we can think of them separately when differentiating:f(x)= x^3 f'(x)= 3x^2g(x)= e^x g'(x)= e^xdy/dx= (3x^2e^x)+ (x^3e^x)
a) First, we need to factorize (x2+x-6) = (x-2)(x+3). Therefore, g(x) = x/(x+3) + 3(2x+1)/(x-2)(x+3) = x(x-2)/(x-2)(x+3) + 3(2x+1)/(x-2)(x+3) = (x2-2x + 6x +3)/(x-2)(x+3) = (x2<...
Part A)Expand numerator in the integral to get 14x^(2) - 2xe^(-2x)-5Now divide by denominator to get 14x - 2e^(-2x) - 5/xNow integrate to get 7x^(2) + e^(-2x) - 5ln(x)Part B)Get all components of y on the...
←
254
255
256
257
258
→
Internet Safety
Payment Security
Cyber
Essentials